Fertility preservation in the female cancer patient. Issue 8 (3rd October 2014) - Ross, Lauren; Chung, Karine; Macdonald, Heather
ABSTRACT Hundreds of thousands of young women are diagnosed with cancer each year, but due to advances in screening, diagnosis, and treatment, survival rates have improved dramatically. With improved survival, long‐term effects of cancer treatment including infertility need to be addressed and should be discussed as soon as possible. Oncologists should be familiar with their patients' risks of infertility and available options for fertility preservation and future reproduction. J. Surg. Oncol. 2014; 110:907–911. © 2014 Wiley Periodicals, Inc.